STUDENTS’ FIRST LANGUAGE: HOW DOES IT INFLUENCE STUDENTS’ PRONUNCIATION? - Puspitasari, Desi; Sa’adah, Nur (J-ELLiT (Journal of English Language, Literature, and Teaching), 2022)
This paper aims to identify how the student’s first language (L1) accent influences students' pronunciation, especially in English consonants. It also investigates students' difficulties in pronouncing English consonants. This study employed descriptive qualitative. Data was collected using observation, interviews, and recordings. The data were gathered from the participants' behavior. It was taken from their written and oral performances. The participants in this study were 6th-semester students of IAIN Ponorogo who had already passed the pronunciation and phonetics subjects. In addition, the students’ L1 was Javanese. The findings revealed that students L1 influenced their pronunciation. They have difficulty pronouncing consonant sounds such as /ʒ, v, θ, ð, z, ʃ, d, ʧ, ʤ].